Transitioning from anatomic landmarks to ultrasound guided central venous catheterizations: guidelines applied to clinical practice. Issue 4 (July 2017) - Oom, Rodrigo; Casaca, Rui; Barroca, Rita; Carvalhal, Sara; Santos, Catarina; Abecasis, Nuno
Introduction: Centrally inserted central catheter (CICC) insertion is a commonly performed procedure that may give rise to different complications. Despite the suggestion of guidelines to use ultrasound guidance (USG) for vascular access, not all centers use it systematically. The aim of this study is to illustrate the experience with ultrasound in CICC placement at a high-volume oncological center, in a country where the landmark technique is standard. Methods: Retrospective analysis of a prospective database was performed on CICC placement under USG in the Central Venous Catheter Unit of Instituto Português de Oncologia de Lisboa Francisco Gentil, from 2012 to 2015. Results: Three thousand five hundred and seventy-two procedures were recorded. From 2728 CICC placements, 1187 (43.5%) were done using USG. The majority of CICC placements were successful without immediate complications (96.1%). In 55 cases (4.6%), more than three attempts were necessary to puncture the vein. Pneumothorax occurred in 5 cases (0.4%) and arterial puncture was registered in 41 cases (3.5%). An increasing use of USG for placing CICCs was planned and observed over the years and, in the last year of the study, 67.3% of the CICC placements were with USG. Conclusions: CICC placement with USG is a safe and effective technique. Despite some resistance that is observed, these results support that it is worth following the guidelines that advocate the use of the USG in the placement of CICC.